Psy-Zing up the Mainstreaming of "Gangnam Style": Embracing Asian Masculinity as Neo-Minstrelsy?. (July 2015) - Park, Michael K.
Through the media mania of Psy's "Gangnam Style, " this paper examines the ideological implications of the video's crossover appeal and its celebrated reception on U.S. national television. This paper analyzes whether the celebratory reception of "Gangnam Style" offer alternative discourses or reinforce ideological constructions of Asian masculinity. A critical decoding of the audiovisual text and Psy's U.S. media appearances identifies the ideological implications that reflect the emasculation discourse that situates Asian masculinity as neo-minstrelsy. Psy's television appearances indicate that his celebratory embrace is due in part because his image and physicality conform to racialized constructions in the larger body politic. This inquiry provides critical insight into how the popular embrace of audiovisual text reflects the emasculation discourse that defines Asian men.